Urgensi Pemenuhan Kebutuhan Dasar Psikologis Peserta Didik dalam Meningkatkan Kualitas Proses Pembelajaran di Sekolah Dasar - Mustikaati, Wina; Radianty, Adya Pramudya Dwi Permata; Hendranti, Alfia Habwah; Nurpadilah, Dila; Marlina, Nina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses the importance of fulfilling students' basic psychological needsautonomy, competence, and relatednesswithin the learning context based on Self-Determination Theory (SDT). Autonomy refers to the sense of independence in making learning decisions, competence relates to the effectiveness in mastering academic tasks, and relatedness reflects the feeling of being accepted and valued within a social environment. This study draws on recent research that demonstrates how meeting these three needs significantly enhances students intrinsic motivation, learning engagement, resilience to academic pressure, and psychological well-being. The findings emphasize the crucial role of teachers, parents, and the social environment in supporting students' basic needs through autonomy support, structured learning, and emotional involvement. The practical implication of this study highlights the necessity for learning strategies that are more responsive to students psychological needs in order to create an inclusive, meaningful, and sustainable educational environment.